TINJAUAN PUASA DALAM PERSPEKTIF KESEHATAN MENURUT IBNU SINA - Setiya Ningrum, Riyani Wahyu; Nadiah, Nadiah; Kunaenih, Kunaenih (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Health is a valuable blessing for humans. If someone is unwell, it will disrupt their activities such as work and prayer. However, in reality, some people do not know that fasting can maintain body health if it is carried out according to the correct rules both in terms of health science and Islamic religious teachings. This research uses qualitative methods through a library research approach. Where this method focuses on research through journal literature, books, and books to search for data and information related to the discussion. The research results explain that fasting is the most effective and efficient way to maintain health. Fasting has two functions, namely as health therapy and self-control over food consumption. Ibnu Sina, who was a famous figure in the fields of religion and medicine, explained that fasting can be used as a therapy to treat various diseases. As for fasting in health science, there are procedures for carrying out fasting, namely not just consuming any food, drinks, and other activities at dawn or breaking the fast. Meanwhile, in Islamic teachings, the procedure for fasting is that if fasting is obligatory, you have to intend it first, which is done before imsak, unless fasting is sunnah, then it is permissible. After that do sahur. In this case, Islam strongly recommends sahur because it brings blessings. Upon arrival at Imsak, you are expected to start fasting until the sun sets, leaving behind anything that could break the fast.